PERSEPSI WISATAWAN TERHADAP POLISI PARIWISATA di DIREKTORAT PENGAMANAN OBJEK VITAL DIT PAM OBVIT POLDA RIAU - Santika, Isnun Jaka; Arief, Andi M. Rifiyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research purpose for knowing what is Tourism Opinion About Tourism Police on Dit Pam Obvit Riau Province Police Departement and for knowing what is tourism want on destination object for tourism pleasure. This research uses quantitative method to analyzes the appointed problem. The samples by using accidental sampling. Whereas, the data accumulation technique of this research uses observation, questionaire, and interview. To establish interval’s length, it uses likert scale measuring. Based on the research that has been done, the responses of respondents regarding the Values of Tourism Police is the most important variable that affect the image of tourism police because the discipline indicator is the highest point selected by the respondents. Key word : Perception, Image, Discipline, Tourism Police in Pekanbaru, Riau Province.